Application of the Point Stress Criterion to Assess the Bond Strength of a Single-Lap Joint - Sajikumar, K.S.; Asok Kumar, N.; Nageswara Rao, B. (Проблемы прочности, 2014)
Finite element analysis has been carried out to obtain the interfacial stresses in a single lap joint using a special 6-node isoparametric element for adhesive layer. The analysis results are found to be in good agreement with the closedform solution of Goland and Reissner. The peak normal and shear stresses found in the adhesive layer at the edges of the joint are due to stress singularity. The bond strength of the single-lap joint is estimated considering one of the stress fracture criteria known as the point stress criterion. Bond strength estimates are found to be reasonably in good agreement with existing test results.